Respuestas
Respuesta dada por:
0
Respuesta:
Hølâ! .
Procedimiento:
-5{-8[5+(7+6)]+1}
= Se resuelve lo del paréntesis
-5{-8[5+(13) ]+1}
= -5{-8[ 18]+1}
= -5 {-8[19]
= -5 { 8 - 19 = 11
= -5 { 11}
= 5 - 11
= 6
Para que te aprendas la conjugación
te dejaré una tabla
Adjuntos:
![](https://es-static.z-dn.net/files/db8/061b6ff89a20d87e53fc3b91780e09db.jpg)
Respuesta dada por:
0
Respuesta:
-5{-8[5+(7+6)]+1}
-5{-8[5+13]+1}
-5{-8+18]+1}
-5{10+1}
-5+11
6
Preguntas similares
hace 6 años
hace 6 años
hace 9 años